Housing Scenario Among the Poor and Marginalized Non-Urban Households: a Case Study Indira Awaas Yojana: Exploring the Housing Scenario and 'Belongingness' Among Non-Urban Poor and Marginalized Households: A Case Study of Indira Awaas Yojana (Journal of Advances and Scholarly Researches in Allied Education, 2013)
There are three basic necessities in life: food,clothing, and shelter. While all three are equally essential, the third oneplays the more important role of harnessing a feeling of"belongingness" to the household/family.